Identification of the standby intervals in the business processes based on analysis of the sequence of events - Чалый, Сергей Федорович; Левыкин, Игорь Викторович (Technology audit and production reserves, 2016)
Business processes that share resources are studied. It is shown that reduction of control efficiency of these processes associated with waiting for access to shared resources. The necessary and sufficient conditions for the occurrence of standby intervals during the process execution are identified based on the study of business processes logs. A method for identifying standby intervals of process resources is proposed based on the attribute analysis, recorded in the event log, in the case that the number of available resource varies during process execution. The method allows to obtain association rules, which establish a change connection of the event attributes to the transition from the process action to the expectation interval. The inclusion of such rules in the business process model, which is obtained by the methods of process mining, allows to predict the emergence of delays in the process implementation. This method creates conditions for improving the process control efficiency by reducing delays in practice.